Alignment and embodiment in a play script writing process: A sociocognitive perspective - Eka Margianti Sagimin; Setiono Sugiharto (JOALL (Journal of Applied Linguistics and Literature), 2023)
Recent development in second language acquisition scholarship has advanced our understanding of how language is acquired by aligning the mind, body, and socio-material world.  Although many studies have been conducted from this perspective, more study on alignment focusing on writing a play script story in literature is needed. Drawing upon the idea of socio-cognitive alignment, this study investigated English literature student interactions during the process of writing a play script. It aims were to find out how mind-body-world as socio-cognitive alignment could contribute to a meaning-making process during writing a play script. A moment analysis was used as a method for analyzing data which were elicited from an audio/videotape recording and semi-structured interviews using a digital platform.  Results revealed that the integration of mind, body, and world was well-coordinated during the process of writing the play script. That is, the integration of mind-body-world was evident in how the students employed both verbal resources and other multimodalities in working with literary works and fiction. The study also demonstrated the importance of alignment and interaction for the development of fiction writing and language competence of EFL students.